Analisis Kemampuan Mind Map Siswa Sekolah Menengah Atas pada Mata Pelajaran Fisika di Surabaya - Catur Prasetya Nugraha; Setyo Admoko; Utama Alan Deta (Department of Physics Education, Universitas Mataram, 2020)
Mind Map is a method or way of taking notes creatively by utilizing the work of the two brains as outlined on paper in the form of pictures, symbols, writing and colors. The purpose of this study was to analyze the use of Mind Maps in student learning activities in physics subjects and to find out students' abilities in making Mind Maps. This research is included in descriptive qualitative research using questionnaires and interviews as well as the results of high school students' Mind Map products. The number of respondents was 243 students from SMA Negeri 11 Surabaya, SMA Negeri 12 Surabaya, SMA Negeri 13 Surabaya and SMA Wijaya Putra Surabaya. As for the Mind Map product, the researchers collected 123 Mind Maps. The results showed that 93.8% of students knew and understood the Mind Map and 60.5% answered that they never made a Mind Map in physics lessons. It was found that students' mistakes in making Mind Maps were that students still ignored the Mind Map format in the categories of images, colors and branches. So it can be concluded that the use of Mind Maps in student learning activities in physics subjects is still lacking or rarely used and the ability of students' Mind Maps is included in the good category but there are still errors or inappropriate formats in making the Mind Map.